NONDESTRUCTIVE CHARACTERIZATIONS OF ALKALI ACTIVATED FLY ASH AND/OR SLAG CONCRETE - Arkamitra Kar; Udaya B. Halabe; Indrajit Ray; Avinash Unnikrishnan (European Scientific Journal, ESJ, 2013)
In recent years, the alkali activated material (AAM) concrete is emerging as a sustainable and green alternative to traditional portland cement (PC) concrete. In order to widen its applications, more information on correlations among its mechanical and physical properties is required. To address the issue this paper studies the relationships between compressive strength, dynamic modulus of elasticity, and ultrasonic pulse velocity of various AAM concrete mixtures with fly ash and/or slag as precursors cured at different temperatures at both unstressed and stressed conditions. The results show that effective relationships can be established to predict compressive strength and modulus of elasticity from the ultrasonic pulse velocity with reasonable accuracy for wide range of AAM concrete mixes.